View of the Renin-Angiotensin System in Acute Kidney Injury Induced by Renal Ischemia-Reperfusion Injury - Karimi, Farzaneh; Maleki, Maryam; Nematbakhsh, Mehdi (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Renal ischemia-reperfusion injury (RIRI) is a sequence of complicated events that is defined as a reduction of the blood supply followed by reperfusion. RIRI is the leading cause of acute kidney injury (AKI). Among the diverse mediators that take part in RIRI-induced AKI, the renin-angiotensin system (RAS) plays an important role via conventional (angiotensinogen, renin, angiotensin-converting enzyme (ACE), angiotensin (Ang) II, and Ang II type 1 receptor (AT1R)) and nonconventional (ACE2, Ang 1-7, Ang 1-9, AT2 receptor (AT2R), and Mas receptor (MasR)) axes. RIRI alters the balance of both axes so that RAS can affect RIRI-induced AKI. In overall, the alteration of Ang II/AT1R and AKI by RIRI is important to consider. This review has looked for the effects and interactions of RAS activities during RIRI conditions.